In vivo expression of Salmonella enterica serotype Typhi genes in the blood of patients with typhoid fever in Bangladesh. - Alaullah Sheikh; Richelle C Charles; Nusrat Sharmeen; Sean M Rollins; Jason B Harris; Md Saruar Bhuiyan; Mohammad Arifuzzaman; Farhana Khanam; Archana Bukka; Anuj Kalsy; Steffen Porwollik; Daniel T Leung; et al. (Public Library of Science (PLoS), 2011)
Salmonella enterica serotype Typhi is the cause of typhoid fever. It is a human-restricted pathogen, and few data exist on S. Typhi gene expression in humans.We applied an RNA capture and amplification technique, Selective Capture of Transcribed Sequences (SCOTS), and microarray hybridization to identify S. Typhi transcripts expressed in the blood of five humans infected with S. Typhi in Bangladesh. In total, we detected the expression of mRNAs for 2,046 S. Typhi genes (44% of the S. Typhi genome) in human blood; expression of 912 genes was detected in all 5 patients, and expression of 1,100 genes was detected in 4 or more patients. Identified transcripts were associated with the virulence-associated PhoP regulon, Salmonella pathogenicity islands, the use of alternative carbon and energy sources, synthesis and transport of iron, thiamine, and biotin, and resistance to antimicrobial peptides and oxidative stress. The most highly represented group were genes currently annotated as encoding proteins designated as hypothetical, unknown, or unclassified. Of the 2,046 detected transcripts, 1,320 (29% of the S. Typhi genome) had significantly different levels of detection in human blood compared to in vitro cultures; detection of 141 transcripts was significantly different in all 5 patients, and detection of 331 transcripts varied in at least 4 patients. These mRNAs encode proteins of unknown function, those involved in energy metabolism, transport and binding, cell envelope, cellular processes, and pathogenesis. We confirmed increased expression of a subset of identified mRNAs by quantitative-PCR.We report the first characterization of bacterial transcriptional profiles in the blood of patients with typhoid fever. S. Typhi is an important global pathogen whose restricted host range has greatly inhibited laboratory studies. Our results suggest that S. Typhi uses a largely uncharacterized genetic repertoire to survive within cells and utilize alternate energy sources during infection.